РЕКОНСТРУКЦІЯ ГЕОХІМІЧНОГО БАР'ЄРА В ПЕРІОД ОПАДОНАКОПИЧЕННЯ ПО ЛОКАЛІЗАЦІЇ МАЛОАМПЛІТУДНОГО НАСУВУ ПЛАСТА l3 (ДОНБАС) - Pymonenko, L.; Balalayev, O.; Baranovskiy, V. (Institute of Geological Sciences of the Ukrainian National Academy of Sciences, 2014)
Reconstruction of local geochemical heterogeneity in low amplitude thrust fault zone formed in sedimentation period is carried out. The interrelation between the conditions of sedimentation and the strength properties of the coal bed line is determined. The analysis of physicochemical mechanisms and the prospective reason of anomaly appearance under aquatic landscapes conditions is given. The quantitative appraisal of oxidizing geochemical barrier gradient is shown. Genetically caused geologic correlation between a tectonic disturbance zone in a coal bed and geochemical barrier location is shown.